Has local government debt crowded out enterprise innovation? - Xiaoxu Zhang; Rongxue Jin (PLoS ONE, 2022)
This paper tests the impact of local government debt on enterprise innovation based on 2011–2017 A-share non-financial enterprise data from Shanghai and Shenzhen Stock Exchanges. The results show that the relationship between government debt and enterprise innovation relationship follows an inverted U-shaped pattern. Endogeneity processing and robustness test result confirm the results of the model built for this study. Heheterogeneity analysis finds that the inflection points of local government debt in large enterprises, non-SOEs (non-state-owned enterprises) and poorly financialized regions are lower. Financing constraints and corporate profits play a part of the intermediary effect in the inverted U-shaped relationship between local government debt and enterprise innovation. Further research shows that Digital finance plays a moderating role in the impact of local government debt on enterprise innovation. Therefore, to keep local government debt scale compliant and to maximize the efficiency of digital finance are of great significance in terms of boosting enterprise innovation and improve economic development.